2022
DOI: 10.3389/fgene.2022.875894
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Scramblases: Role in Cancer Progression and Anticancer Therapeutics

Abstract: Phospholipid scramblases (PLSCRs) that catalyze rapid mixing of plasma membrane lipids result in surface exposure of phosphatidyl serine (PS), a lipid normally residing to the inner plasma membrane leaflet. PS exposure provides a chemotactic eat-me signal for phagocytes resulting in non-inflammatory clearance of apoptotic cells by efferocytosis. However, metastatic tumor cells escape efferocytosis through alteration of tumor microenvironment and apoptotic signaling. Tumor cells exhibit altered membrane feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 139 publications
(151 reference statements)
1
11
0
Order By: Relevance
“…It was found that a high expression of FPR2 was associated with a lower OS in LUAD patients ( 8 ). ANO6 is a member of the TMEM16 family, which was initially discovered as Ca 2+ -activated Cl - ion channels ( 19 ). The TMEM16 family was found to be overexpressed in cancer cells associated with poor prognosis and cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that a high expression of FPR2 was associated with a lower OS in LUAD patients ( 8 ). ANO6 is a member of the TMEM16 family, which was initially discovered as Ca 2+ -activated Cl - ion channels ( 19 ). The TMEM16 family was found to be overexpressed in cancer cells associated with poor prognosis and cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of hPLSCR1 in CHO-K1 cells activated caspase-3 and stimulated the PS biosynthesis (Yu et al 2003). On the other hand, the overexpression of hPLSCR1 showed an important role in various cancer types (Silverman et al 2002;Kuo et al 2011;Behuria et al 2022). hPLSCR1 helps in blood cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The Overexpression of PLSCR1 induces apoptosis and inhibits protective autophagy of NB4 leukemic cells and thus acts as a analytical marker for acute myelogenous leukemia (AML) (Behuria et al 2022). hPLSCR1 is a regulatory protein in Colorectal Carcinoma, Hepato-Pancreatic Carcinoma, Ovarian Cancer, and breast cancer (Silverman et al 2002;Kuo et al 2011;Behuria et al 2022). The overexpressed hPLSCR1 suppresses the tumorigenesis in HEY1B cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, alterations in the spatial organization of plasma membrane lipids have been associated with cancer risk. For example, the loss of PS asymmetric distribution between the exofacial and cytofacial membrane leaflets and increased PS exposure on the surface of malignant cells compared to healthy cells has been recently reported [606][607][608]. Notably, the efficacy of radiotherapy and chemotherapy-based anticancer treatments is dependent on the phenotype of PS exposure [609].…”
Section: Dysregulation Of Membrane Fluidity and Nanocluster Domains A...mentioning
confidence: 99%